Corrosion behaviour of nitrided ferritic stainless steels for use in solid oxide fuel cell devices. (1st April 2020) - Bianco, Manuel; Poitel, Stephane; Hong, Jong-Eun; Yang, Shicai; Wang, Zhu-Jun; Willinger, Marc; Steinberger-Wilckens, Robert; Van herle, Jan
Highlights: The usefulness of nitriding as pre-treatment for SOFC interconnects is tested. In situ oxidation of samples was recorded with environmental SEM. The electrical properties of the steels are not clearly improved. Nitriding demonstrated to decrease chromium evaporation with porous coating. No intergranular corrosion is observed in the samples. Abstract: Plasma nitriding was applied to ferritic stainless steel substrates to improve their performances as interconnects for solid oxide fuel cell devices. The samples underwent electrical conductivity test and SEM/EDS, TEM/EDS, environmental-SEM analyses. The first stages of corrosion were recorded in-situ with the e-SEM. Nitriding is effective in limiting the undesired chromium evaporation from the steel substrates and accelerates the corrosion kinetics, but its influence of the electrical conductivity is ambiguous. No intergranular corrosion is found in the steel substrate after long time operation. Nitriding helps commercially competitive porous coating to improve chromium retention properties of metal interconnects.